Improvement of technological solution of erection large-span coatings by lifting modules - Ignatenko, O. (Ways to Improve Construction Efficiency, 2024)
After studying the organization and technological aspects of existing solutions for lifting large-span coatings through pulling and pushing, a new technological approach for erecting coatings using lifting modules was developed. According to the developed solution, first, by methods of free lifting using self-propelled boom cranes, twin columns of the frame, inter-column beams and bundles are mounted. On the foundations between the paired columns are placed lifting modules, which consist of hydraulic jacks and lifting platforms. Installation column heads are installed on lifting platforms. The external surfaces of carcass columns are secured with lifting retainers that are made of cantilevered support platforms, hydraulic cylinders, and movable crossbars. On low scaffolding, structural and technological blocks of coatings are increased. At that bearing crossbars of coatings are introduced into space between paired columns of frame and lowered onto heads of mounting columns. At the second stage of installation works by method of pushing out the coating is moved to the design height provided that supporting crossbars of the coating are supported on the heads of growing installation columns. In the process of growing the sections of the installation columns, the load from the raised coating and sections of the installation columns is alternately transferred to the hydraulic jacks of the lifting modules and the girders of the lifting locks. According to the developed solution, all the processes of growing the sections of installation columns and moving the roof girders from the foundation level to the level of the heads of the frame columns are automated Work on the construction of coatings can be performed in conditions of dense buildings on the site, the size of which does not exceed the overall dimensions of the rising coating. The volumes of high-altitude works have been reduced to operations for fixing the bearing crossbars of the coatings between the heads of the paired columns of the frame, which allows to significantly reduce the total time of lifting works.